Holistic Management of Chronic Headache and Co-morbidities in Primary Care : A Family-Centered Approach - Rosita, Rita; Hidayati, Nurul; Septian Prihatma, Wika (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2025)
Chronic headaches, particularly tension-type headaches (TTH), pose a significant burden in primary care, often co-occurring with various health and psychosocial challenges. This case report highlights the importance of a holistic, family-centered approach to effectively manage such complex presentations. We present the case of a 52-year-old male, a self-employed electrical installation worker, presenting with a one-week history of worsening daily headache, described as pressing and heavy, predominantly occipital spreading to frontal regions, rated 7-8/10 on the pain scale. The patient has a history of hypertension since 2019, regularly taking amlodipine 10mg, and is classified as overweight (24.2 kg/m2). He reports reduced sleep quality due to work-related stress and a tendency to internalize problems. The patient's TTH appears exacerbated by poor sleep hygiene, work-related stress, and reduced physical activity during the pandemic. While hypertension is not directly correlated with TTH pathophysiology, it adds to the overall health risk. A comprehensive intervention included pharmacotherapy (paracetamol 1000 mg, amlodipine 10mg) and extensive non-pharmacological strategies focusing on sleep hygiene, stress management, increased physical activity, and improved communication within the family. Despite a